COMPETENCIES OF TECHNOLOGY AND LIVELIHOOD EDUCATION TEACHERS - Guiquing, Fernando (International Journal of Arts, Sciences and Education, 2024)
This research article on the Competencies of Technology and Livelihood Education Teachers determined the profile of the participants in terms of school, highest educational attainment, and length of service as a TLE teacher and investigated the level of competencies of the Technology and Livelihood Education teachers in two TLE Components, which are the Home Economics and Information and Communication Technology. The descriptive research design was utilized to describe the profile of the participants, the level of competencies of the TLE teachers, and the teachers’ teaching performance. There were 22 Junior high school TLE teachers from the six public schools of Cagayan. The teacher-participants were chosen through total enumeration. The researcher utilized a survey questionnaire validated by experts. Documentary analysis was done for the teachers’ teaching performance. Results show that the competencies of the TLE teachers are high, with outstanding teaching performance based on IPCRF.